Socio-demographic and clinical profile of patients visiting general practitioner clinic for general health check-up in a tertiary care center of Nepal: a descriptive cross-sectional study - Tiwari, Sanjeeb; Poudel, Bipin; Bista, Apeksha; Maharjan, Bunu; Maharjan, Kritima; Shrestha, Shubham (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: General Practitioners (GPs) are vital in preventive medicine and health promotion due to their frontline contact with the public. However, more research is needed on the sociodemographic and clinical profiles of the patients seeking care from general practitioners. Understanding these profiles can aid in developing effective interventions and strategies to enhance patient and caregiver participation in healthcare decisions. This study aimed to evaluate the sociodemographic and clinical profile of patients visiting a general practitioner clinic for general health check-ups in a tertiary care center in Nepal. Method: A descriptive cross-sectional study was conducted in the Tribhuvan University Teaching Hospital, Maharajagunj, Kathmandu, Nepal from December 2020 to January 2021, including all the patients visiting the general practitioner clinic for general health check-ups. Relevant data were extracted using a structured proforma. Data was entered using Microsoft Excel 2019 and analyzed using IBM SPSS Statistics version 16.0. Result: Out of 115 patients, the mean age was 45 + 14 with a female predominance of 60 (52.2%). 46 (40%) of the patients visited for general checkups which were followed by the majority of musculoskeletal problems. 38 (33.3%) of the participants were overweight. Regarding the lipid profile, the patient exhibited borderline abnormal levels, indicating the necessity to assess for screening, monitoring, and potential intervention. Conclusion: Socio-demographic factors, existing medical conditions and life-style elements such as obesity and abnormal lipid profiles influence visits to primary care physicians. This information can aid in planning, resource allocation, prioritizing research, policymaking, guideline development, and training primary care professionals.